The immune phenotypes and different immune escape mechanisms in colorectal cancer - Mao, Yihao; Xu, Yuqiu; Chang, Jiang; Chang, Wenju; Lv, Yang; Zheng, Peng; Zhang, Zhiyuan; Li, Zhiqiang; Lin, Qi; Tang, Wentao; Zhu, Dexiang; Ji, Meiling; et al. (Frontiers in Immunology, 2022)
The tumor microenvironment (TME) plays a crucial role in tumor progression and metastasis. However, the immune phenotypes of colorectal cancer (CRC) and the underlying immune escape mechanism have not been studied sufficiently. A total of 1802 and 619 CRC samples from the microarray and TCGA cohorts were enrolled, respectively. The ssGSEA algorithm and unsupervised clustering were used for TME cell infiltration speculation and immune phenotype recognition in the above cohorts. A total of 447 samples from Zhongshan Hospital were collected for validation. Immunohistochemistry was performed in this cohort to quantify TME cell infiltration. The single-cell RNA-seq (scRNA-seq) data of 252,940 cells from 60 CRC samples was analyzed for further mechanistic exploration. CRC samples can be classified into three distinct immune phenotypes. Subtype 1, the immune-active subtype, was characterized by high infiltration of activated adaptive immune cells. Subtype 2, the immune-desert subtype, featured high tumor purity and low infiltration of immune and stromal cells. Subtype 3, the stroma-rich subtype, had high infiltration of stromal cells. The stroma-rich subtype conferred a significantly worse prognosis. The three subtypes had different immune escape mechanisms. The immune-active subtype has the highest immune checkpoint expression level. In comparison, the immune-desert subtype had the lowest immunogenicity and defective antigen presentation. The stroma-rich subtype lacked activated immune cells. In conclusion, distinct immune phenotypes and immune escape mechanisms may provide inspiration and direction for further research on CRC immunotherapy.